2017
DOI: 10.1088/1361-6463/aa9b60
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the thermal stability of Nb:TiO2−xsamples for uncooled infrared detectors

Abstract: In order to reduce the sun-burn effect in a sample of the bolometric material Nb:TiO2−x, oxygen annealing was carried out. This effect can be examined by comparing thermal stability test results between the as-deposited and oxygen-atmosphere-annealed samples under high-temperature exposure conditions. Structural studies confirm the presence of amorphous and rutile phases in the as-deposited and annealed samples, respectively. Composition studies reveal the offset of oxygen vacancies in the Nb:TiO2−x samples th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The diffusion mechanism of oxygen during annealing in the oxygen atmosphere is exhibited in figure 14(a). It is clearly shown that oxygen vacancies are offset by oxygen atoms diffusion during high-temperature annealing [60]. As shown in figure 14(c), the sample deposited at room temperature does not show the Raman spectra of TiO 2−x , indicating that the film is amorphous.…”
Section: Thermal Stability Of Nb-tio 2−xmentioning
confidence: 94%
See 3 more Smart Citations
“…The diffusion mechanism of oxygen during annealing in the oxygen atmosphere is exhibited in figure 14(a). It is clearly shown that oxygen vacancies are offset by oxygen atoms diffusion during high-temperature annealing [60]. As shown in figure 14(c), the sample deposited at room temperature does not show the Raman spectra of TiO 2−x , indicating that the film is amorphous.…”
Section: Thermal Stability Of Nb-tio 2−xmentioning
confidence: 94%
“…They annealed the samples at a high current to remove the ghost image, but the resistivity of annealed samples decreased. Therefore, increasing the current for annealing is not a fundamental solution to the ghost image [60].…”
Section: Thermal Stability Of Nb-tio 2−xmentioning
confidence: 99%
See 2 more Smart Citations
“…However, one limiting factor is that the synthesis of this material requires critical oxygen and temperature conditions and suitable sputter targets . Another material system that has shown good promise for use as an uncooled BM is the nonstoichiometric TiO 2– x /TiO x films. These films are mostly grown with reactive magnetron sputtering or ALD with a near-RT absolute TCR value as high as 9%/K . Thermal annealing and Nb doping have proved to be successful schemes toward improving the bolometric response of these Ti oxide films.…”
mentioning
confidence: 99%